Financial health of small and medium-sized companies in the Visegrad countries - Tomáš Pražák (e-Finanse: Financial Internet Quarterly, 2019)
SMEs are a major provider of jobs, contribute to promoting the social and economic cohesion of regions and, in particular, they are important for regions facing high unemployment or lower economic development. The importance of assessing a company's financial performance has been steadily rising in recent years. The paper aims to evaluate to what extent the financial situation of a company, especially the risk of financial distress and bankruptcy, is influenced by the macroeconomic environment defined by fundamental macroeconomic variables. The analysis of the interrelationships will be carried out at the national level for Visegrad countries. The criterion for financial distress is defined not only by capital restructuring of the company or extensive layoffs, but also as the results of the negative effect of the macroeconomic environment. To achieve the goal of the paper, predictive bankruptcy models of financial distress based on financial analysis of enterprises will be used as well as regression analysis and correlation analysis. The observed period for analyses will be from 2009 to 2016. It seems appropriate to pay particular attention to examining the impact of economic growth, and the exchange rate on the financial situation of the enterprise. These indicators play an important role in defining internal and external economic equilibrium, which is also reflected in the functioning of individual businesses and sectors.
Keywords: E01; M21; 330; corporate financial distress; bankruptcy; macroeconomic environment; Visegrad countries; regression analysis